Implementation Of Presidential Regulation Number 59 Of 2019 Concerning Control Of Transfer Of Function Of Rice Land (Study At The Jombang Regency Land Office) - Sunardi, Sunardi; Muhibbin, Moh.; Pratiwi Wiranita, Indriet (Universitas Islam Malang, 2024)
Abstract : Controlling the conversion of paddy fields is one of the strategies to increase domestic rice production, so it is necessary to accelerate the determination of the Map of Protected Paddy Fields (PLSD). So far, Law no. 41 of 2009 concerning Protection of Sustainable Food Agricultural Land, along with Government Regulation (PP) No. 1 of 2011 concerning the Determination and Transfer of Functions of Sustainable Agricultural Land and Presidential Regulation Number 59 of 2019 concerning control of the conversion of paddy fields. The narrowing of agricultural land in Jombang Regency is due to the construction of housing which is increasing every year. The formulation of the problem 1) How is the implementation of Presidential Regulation Number 59 of 2019 regarding the conversion of paddy fields as a form of government prevention of the conversion of paddy fields at the Land Office of Jombang Regency 2) What are the obstacles and efforts to overcome obstacles to implementing Presidential Regulation Number 59 of 2019 regarding the conversion of paddy fields in managing land at the Jombang District Land Office, 3) What is the legal protection for paddy fields that have been protected since the enactment of Presidential Decree Number 59 of 2019 concerning the conversion of paddy fields in Jombang Regency. By using empirical research methods with research locations Jombang district land office. The results of the research on the implementation of Presidential Decree No. 59 of 2019 concerning the conversion of paddy fields as a preventive form for the government regarding the conversion of paddy fields at the Jombang Regency Land Office, in theory have not gone smoothly, but for signs for developers not to free up paddy fields as comfortably as possible used for housing or settlements. However, on the other hand, it creates a new problem for individual applicants because for individual applicants who wish to apply for separation of rights to inherited or non-inherited land, if the RTR block map includes the LSD map. Obstacles and efforts to overcome obstacles to the implementation of Presidential Regulation Number 59 of 2019 concerning the conversion of paddy fields in land management at the Jombang Regency Land Office, the form of settlement includes 1) Completion in the context of Completing Map Data of Protected Paddy Fields 2) Completion of Protected Paddy Fields in Accordance with Areas/Zones of Food Crops in the Spatial Plan 3) Settlement of Protected Paddy Fields that are Not In Accordance with the Areas/Zones of Food Crops in the Spatial Plan. Legal protection for paddy fields that have been protected since the enactment of Presidential Decree No. 59 of 2019 concerning the conversion of paddy fields in Jombang Regency. Food security will be maintained and to maintain protected paddy fields so they don't become residential land.Keywords: LSD, BPN, Rice fields, housing